2022
DOI: 10.1136/ejhpharm-2022-003371
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives of successful adalimumab biosimilar transitioning in Crohn’s disease: an interview study

Abstract: ObjectivesTransition from originator biological medicines to their biosimilar equivalents is now part of routine clinical practice, but there is little understanding of patient experiences, which influence adherence and overall satisfaction with care. Understanding this will help ensure future switches adequately address patients’ concerns and expectations leading to better outcomes for all stakeholders.Method35 patients participating in a clinical trial including an open-label transition event from originator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The findings highlight the importance of keeping patients’ experiences with the biosimilar treatment at the forefront of future brand changes. Consistent with previous research, participants’ experiences with the adalimumab injection (i.e., less pain and ease of device) were an important aspect of their satisfaction with the transition ( 15 ). Participants also reported that the biosimilar package changed, as alcohol wipes were not provided.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings highlight the importance of keeping patients’ experiences with the biosimilar treatment at the forefront of future brand changes. Consistent with previous research, participants’ experiences with the adalimumab injection (i.e., less pain and ease of device) were an important aspect of their satisfaction with the transition ( 15 ). Participants also reported that the biosimilar package changed, as alcohol wipes were not provided.…”
Section: Discussionsupporting
confidence: 83%
“…Understanding patients’ experiences of the adalimumab transition is particularly important as the biologic is self‐administered at home. As such, patients often experience a change in device (and branding) and are also more removed from their healthcare teams than when administered in the hospital ( 15 ). The present study explores rheumatology patients’ satisfaction with the biosimilar and care supplies, the supply of the biosimilar and logistics of the transition, administrative burdens, information and education, and availability of support.…”
Section: Introductionmentioning
confidence: 99%